Autophagy‐Induced Apoptosis in Lung Cancer Cells by a Novel Digitoxin Analog. Issue 4 (April 2016) - Kulkarni, Yogesh M.; Kaushik, Vivek; Azad, Neelam; Wright, Clayton; Rojanasakul, Yon; O'Doherty, George; Iyer, Anand Krishnan V.
Abstract : We have synthesized a novel derivative of Digitoxin, termed "MonoD", which demonstrates cytotoxic effects in lung cancer cells with much higher potency as compared to Digitoxin. Our data show that within 1 h of MonoD treatment, H460 cells showed increased oxidative stress, increased formation of autophagic vacuoles, and increased expression of pro‐autophagic markers Beclin‐1 and LC3‐II. Cells pretreated with MnTBAP, a superoxide scavenger not only lowered superoxide production, but also had lower levels of LC3‐II and Beclin‐1. Prolonged treatment with MonoD‐induced apoptosis in lung cancer cells. We investigated MonoD‐dependent regulation of Akt and Bcl2, proteins that are known regulators of both autophagy and apoptosis. Molecular and pharmacologic inhibitors of Bcl2 and Akt, when combined with MonoD, led to higher expression of LC3‐II and Beclin‐1 as compared to MonoD alone, suggesting a repressive effect for these proteins in MonoD‐dependent autophagy. Pretreatment of cells with an autophagy inhibitor repressed the apoptotic potential of MonoD, confirming that early autophagic flux is important to drive apoptosis. Therapeutic entities such as MonoD that target multiple pathways such as autophagy and apoptosis may prove advantageous over current therapies that have unimodal basis for action and may drive sustained tumor regression, which is highly desirable. J. Cell. Physiol. 231: 817–828, 2016. © 2015 Wiley Periodicals, Inc.